Scientific - innovative methods of teaching the subject of life safety in the Republic of Uzbekistan (Zien Journal of Social Sciences and Humanities, 2022)
The article deals with the issues of modern scientificdevelopment of an integrated management system for life safety and social insurance in the context of transition to a market model of economic development.